Mortalidad y predictores de mortalidad en niños menores de 15 años que adquirieron el VIH por transmisión madre-hijo en el Paraguay - Barreto, Gloria Celeste Aguilar (2017)
Introduction: Efforts have been made in Paraguay to improve the response to HIV infection. In the context of the Sustainable Development Goals, it is important to evaluate the impact of interventions in pediatrics. Objective: To estimate the mortality rate and predictors in children who acquired HIV through mother-to-child transmission between January 2000 and December 2014. Material and methods: An observational, cohort-type study was performed with follow-up from the birth of children and adolescents who were <15 years of age at the time of recruitment. Data were obtained from clinical records. Death data were recorded from medical records and confirmations of deaths from death certificates. Survival analysis techniques were used to estimate the incidence of death Results: A total of 302 subjects were included, 216 (71.6%)% under six years of age,148 ( 51.0%) male, and 214( 70.9%)% of the main metropolitan area. There were 52 deaths (17.2%) with an overall mortality rate of 2.06 deaths / 100 personyears. Children with hemoglobin ≤9 g/dL were 2 times more likely to die compared to hemoglobin > 9 g / dL [ (hazard ratio; 2.27, (95% CI: 1.01, 5.10) ]. The risk of death was 74% lower for children diagnosed in the period ≥ 2010 compared to those diagnosed before 2010 [hazard ratio ; 0.26, (95 CI%, 0.07-0-88)] . Conclusion: The mortality of children with HIV in Paraguay is high, and anemia is associated with mortality. Improving prenatal care and pediatric follow-up in an effort to early diagnose children infected by mother-to-child transmission should be an integral part of the health care offered to the child with HIV infection.